Ветеринарно-санітарна експертиза продуктів забою курчат-бройлерів за збагачення раціону цитратом наномолібдену та кормовою добавкою "Пробікс" - Головко, Наталія Петрівна (НУБіП України, 2016)
Дисертація на здобуття наукового ступеня кандидата ветеринарних наук за спеціальністю 16.00.09 – ветеринарно-санітарна експертиза. – Національний університет біоресурсів і природокористування України, Київ, 2016. Дисертаційну роботу присвячено дослідженню впливу на показники продуктивності, а також якості й безпечності продуктів забою курчат-бройлерів нутріцевтиків цитрату наномолібдену в концентрації 0,24 мг/дм3 води три доби поспіль з інтервалом у три доби та кормової добавки «Пробікс» у запропонованій виробником дозі з розрахунку 600 г/т корму з 5 до 28 доби, із 28 по 42 добу життя – 300 г/т, з 5 до 42 доби відгодівлі. Вперше в Україні експериментально обґрунтовано оптимальну концентрацію цитрату наномолібдену під час відгодівлі птиці. Експериментально підтверджено позитивний вплив нутріцевтиків на показники якості та безпечності м’яса і продуктивності курчат, в порівнянні з контролем. Науково обґрунтовано, що за комплексом ветеринарно-санітарних параметрів продукти забою курчат-бройлерів, яким упродовж відгодівлі застосовували нутріцевтики цитрат наномолібдену, а також кормову добавку «Пробікс», за органолептичними, фізико-хімічними, токсико-біологічними, макро- та мікроскопічними, бактеріологічними показниками є якісними і безпечними, отже, можуть бути дозволені до реалізації без обмежень.
Thesis on the Academmic degree of the Candidate of the Veterinary Science with the field of specialization 16.00.09 – veterinary-sanitary examination. – The National University of Life and Environmental Sciences of Ukraine, Kyiv, 2016. Thesis Papers is devoted to the analysis of the influence which is had on the indicators of productivity as well as quality and safety of slaughter production of broiler-chickens by nutraceutical citrate which concentration is 0.24 mg/dm³ of water within three days one after another at three days interval and by food additive «Probics» which dose is proposed by the producer on the basis of 600 g/t of fodder from the 5th to the 28th day, from the 28th day to 42nd day of living – 300 g/t, from the 5th to the 42nd day of fattening. The optimal dose of nanomolibden citrate in the process of fowls’ fattening has been theoretically and experimentally argued in Ukraine for the first time. There are experimental proves of the positive influence which is had by nutraceutical on the indicators of chickens productivity, and on the physiological and morphological parameters of the organism in comparison with the controlled variants. It is scientifically proved that the products of slaughter of broiler-chickens, which have been receiving nutraceutical citrate of nanomolibden and complex food additive «Probics» in the process of fattening are qualitative and safe, and as well can be allowed without any limits in accordance to the complex of veterinary-sanitary parameters, and in accordance to organoleptic, physical-chemical, toxic-biological, macro- microscopical and bacteriological indicators.
Keywords: ветеринарно-санітарна експертиза; курчата-бройлери; продукти забою; цитрат наномолібдену; кормова добавка «Пробікс»; veterinary-sanitary examination; broiler-chickens; slaughter production; citrate of nanomolibden; food additive «Probics»